Surgical Procedure Joining the Lateral Rectus and Superior Rectus Muscles With or Without Medial Rectus Recession for the Treatment of Strabismus Associated With High Myopia - (:unkn) unknown (SLACK INC, 2014)
Purpose: To evaluate the outcomes of a surgical procedure involving the muscle union of the superior rectus (SR) and lateral rectus (LR) muscles with or without medial rectus (MR) recession for the treatment of strabismus associated with high myopia and the anatomic changes from before and after surgery. Methods: Thirty-five eyes of 20 patients who had undergone a muscle union of the SR and LR muscles with or without MR recession for treatment of acquired strabismus associated with an inferior displacement of the LR and nasal displacement of the SR in magnetic resonance imaging of the orbit due to axial high myopia were observed prospectively. Main outcome measures were the angles of the dislocation of the globe, angles of horizontal or vertical deviations, abductions, and supraductions. The angles of the dislocation of the globe were analyzed using magnetic resonance imaging (1.5 Tesla Magnet; Siemens Symphonia, Munich, Germany). Results: The axial lengths ranged from 26 to 36 mm ( mean: 30.6 +/- 2.8 mm). The angle of dislocation of the globe changed from 178 degrees +/- 10 degrees to 101 degrees +/- 6 degrees, the angle of esotropia changed from 58.6 +/- 2.5 to 6.8 +/- 1.4 prism diopters (PD); and the angle of hypotropia changed from 12.5 +/- 1.3 to 3.3 +/- 1.1 PD postoperatively. Abduction and supraduction improved significantly after surgery. At the 4-year follow-up, the postoperative outcomes were stable. Conclusions: In the treatment of strabismus caused by high myopia, the surgical procedure involving the muscle union of the SR and LR muscles with or without MR recession was effective on both the restoration of the dislocated globe into the muscle cone and the improvement of ocular motility.
Keywords: HEAVY EYE SYNDROME; PROGRESSIVE ESOTROPIA; LOOP MYOPEXY; FIXUS; SURGERY; PATHS